Organizational innovation: a comprehensive model for catalyzing organizational development and change in a rapidly changing world - Annika Steiber; Sverker Alänge (Triple Helix, 2015)
Previous research has found that organizational innovations are important for organizations' long-term competitive advantage and for technical innovations. In spite of this conclusion, organizational innovations remain poorly managed and poorly understood, especially the processes through which organizational innovations are created, diffused, and sustained. There is thus a need for a more comprehensive understanding of mechanisms catalyzing organizational development and change.
Keywords: 330; Creation; Diffusion; Organizational development; Organizational innovation; Sustaining; Model